Interdisciplinary integration across the curriculum - Syed Alwi, Shahab (2009)
In proposing various definitions and taxonomies for the curriculum and in thinking beyond disciplinary units and modalities, current academic discourse is engaged in a process of reconstruction. In all sectors, new technologies have influenced greatly how research is carried out. The impact ofthese same technologies has also influenced the general public's view ofwhat constitutes an appropriate education for the next generation that will enter the labour market. Given the present economic, technological, social and ideological contexts, it is perhaps no surprise that many have called into question the value of a liberal specialized education. When they consider employment prospects, both students and parents question the choice of a liberal education as impressions persist that in today's and tomorrow's marketplace, the skills and competencies of humanities graduates appear to be obsolete. This paper will examine some ofthese assumptions and propose an alternative which redefines the structure of disciplinary teaching and learning and research from an integrated and "interdisciplinary perspective, incorporating the sciences, humanities, and social sciences.